8x2y-4xy=4xy

Subtract 4xy from both sides of the equation.

8x2y-4xy-4xy=0

Subtract 4xy from -4xy.

8x2y-8xy=0

8x2y-8xy=0

Factor 8xy out of 8x2y.

8xy(x)-8xy=0

Factor 8xy out of -8xy.

8xy(x)+8xy(-1)=0

Factor 8xy out of 8xy(x)+8xy(-1).

8xy(x-1)=0

8xy(x-1)=0

Divide each term in 8xy(x-1)=0 by 8x(x-1).

8xy(x-1)8x(x-1)=08x(x-1)

Simplify 8xy(x-1)8x(x-1).

Cancel the common factor of 8.

Cancel the common factor.

8xy(x-1)8x(x-1)=08x(x-1)

Rewrite the expression.

xy(x-1)x(x-1)=08x(x-1)

xy(x-1)x(x-1)=08x(x-1)

Cancel the common factor of x.

Cancel the common factor.

xy(x-1)x(x-1)=08x(x-1)

Rewrite the expression.

y(x-1)x-1=08x(x-1)

y(x-1)x-1=08x(x-1)

Cancel the common factor of x-1.

Cancel the common factor.

y(x-1)x-1=08x(x-1)

Divide y by 1.

y=08x(x-1)

y=08x(x-1)

y=08x(x-1)

Simplify 08x(x-1).

Cancel the common factor of 0 and 8.

Factor 8 out of 0.

y=8(0)8x(x-1)

Cancel the common factors.

Factor 8 out of 8x(x-1).

y=8(0)8(x(x-1))

Cancel the common factor.

y=8⋅08(x(x-1))

Rewrite the expression.

y=0x(x-1)

y=0x(x-1)

y=0x(x-1)

Divide 0 by x(x-1).

y=0

y=0

y=0

The given equation y=0 can not be written as y=kx2, so y doesn’t vary directly with x2.

y doesn’t vary directly with x

Find the Quadratic Constant of Variation 8x^2y-4xy=4xy